Students’ Perception Of Presentation Activities In Learning English Phonology - Nurasiah Anggini; Tiara Putri; Yani Lubis (Universitas Dehasen Bengkulu, 2023)
This research aimed to find out the advantages of presentation activities in learning english phonology. Descriptive qualitative method was used in this research. Data were collected using an interview to gauge the students’ perception of presentation activities in learning english phonology. The population of this research was ten students from TBI 1 in Islamic State University of North Sumatera. The research finding shown that the students had a highly positive and positive attitude about the use of presentations in English phonology lessons. The students believed the presenting activities were educational and helpful in developing their English pronunciation and vocabulary. It could be concluded that the use of presentation activities in learning english phonology gave some advantages to the students at TBI 1.